2022
DOI: 10.1039/d2gc01834a
|View full text |Cite
|
Sign up to set email alerts
|

Depolymerization of post-consumer PET bottles with engineered cutinase 1 fromThermobifida cellulosilytica

Abstract: Bio-recycling of plastic waste is a promising solution to plastic pollution. As one of the most abundant plastic wastes, polyethylene terephthalate (PET) can be degraded by carboxylic ester hydrolases (EC...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 50 publications
(78 reference statements)
1
18
0
Order By: Relevance
“…However, high-level candidate degraders with the ability to produce degradation products such as mono/bis(2-hydroxyethyl) terephthalate (MHET/BHET) and terephthalate (TPA) on an industrial scale are limited and need further approaches to design efficient PET hydrolases as well as to achieve ultra-high-throughput screening from novel resources (Wei et al 2022 ). Among already known candidates, cutinases from thermophilic actinomycetes ( T. fusca , T. cellulosilytica and Saccharomonospora viridis ) (Wei et al 2019 ; Zhang et al 2022 ; Emori et al 2020 ), a leaf-branch compost metagenome-derived cutinase (LCC) (most probably derived from Chloroflexi species; Xi et al 2021 ) (Tournier et al 2020 ; Zeng et al 2022 ) and a thermophilic fungus cutinase from Humicola insolens (commercialized) (Castro et al 2019 ) have been reported to possess a thermostability at more than 70 °C and to accumulate high millimolar level of degradation products. Tournier et al ( 2020 ) reported an efficient process for PET recycling, based on two strategies using amorphized and particulate PET with engineered variants of the LCC.…”
Section: Introductionmentioning
confidence: 99%
“…However, high-level candidate degraders with the ability to produce degradation products such as mono/bis(2-hydroxyethyl) terephthalate (MHET/BHET) and terephthalate (TPA) on an industrial scale are limited and need further approaches to design efficient PET hydrolases as well as to achieve ultra-high-throughput screening from novel resources (Wei et al 2022 ). Among already known candidates, cutinases from thermophilic actinomycetes ( T. fusca , T. cellulosilytica and Saccharomonospora viridis ) (Wei et al 2019 ; Zhang et al 2022 ; Emori et al 2020 ), a leaf-branch compost metagenome-derived cutinase (LCC) (most probably derived from Chloroflexi species; Xi et al 2021 ) (Tournier et al 2020 ; Zeng et al 2022 ) and a thermophilic fungus cutinase from Humicola insolens (commercialized) (Castro et al 2019 ) have been reported to possess a thermostability at more than 70 °C and to accumulate high millimolar level of degradation products. Tournier et al ( 2020 ) reported an efficient process for PET recycling, based on two strategies using amorphized and particulate PET with engineered variants of the LCC.…”
Section: Introductionmentioning
confidence: 99%
“…With the crystal structures of several PHEs elucidated, structure‐based rational designs of PHEs for improved hydrolytic activity and thermostability have been intensively researched and made great progress (Table 1). Reshaping the substrate‐binding pocket by exploring key residues around the binding cleft, [26,29] optimizing electrostatic charge of protein surface, [19a,30] introducing additional interactions (disulfide bonds, [19a,29a,f,30–31] salt bridges, [32] hydrogen bonds, [33] hydrophobic [33–34] and aromatic interactions [35] ), and increasing proline which has a rigid cyclic structure on the side chain [34] for higher thermostability are commonly used strategies. For example, Tournier et al [29a] .…”
Section: Protein Engineering Of Pet Hydrolytic Enzymesmentioning
confidence: 99%
“…15). Second, the surfactant addition and dosage were tested as surfactants have been proven to be an efficient method for accelerating the PET hydrolysis process [39][40][41] . The enzyme concentration was optimized last considering the optimal enzyme loading was correlated with the surfactant addition (Supplementary Fig.…”
Section: The Depolymerization Of Untreated Post-consumer Pet (Pc-pet)...mentioning
confidence: 99%